Italian consensus on treatment of spasticity in multiple sclerosis. (3rd December 2019) - Comi, G.; Solari, A.; Leocani, L.; Centonze, D.; Otero‐Romero, S.; ,
Abstract : Background: Spasticity is a frequent multifactorial manifestation of multiple sclerosis (MS), affecting mostly the chronic courses of the disease. Its impact on patient functioning and quality of life is profound. Treatment of spasticity includes oral and intrathecal anti‐spastic drugs, muscle injections with relaxant agents, physical therapy, electrical and magnetic stimulation and peripheral nerve stimulation, alone or in various combinations. Methods: This Italian consensus on the treatment of spasticity in MS was produced by a large group of Italian MS experts in collaboration with neurophysiologists, experts in the production of guidelines and patients' representatives operating under the umbrella of the Italian Neurological Society, the Associazione Italiana Sclerosi Multipla and the European Charcot Foundation. This guideline was developed in accordance with the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. A total of 11 questions were formulated following the PICO framework (patients, intervention, comparator, outcome). Controlled studies only were included in the analysis. Results: Despite some consistent limitations due to the poor methodological quality of most studies, there was a consensus on a strong recommendation for the use of intrathecal baclofen, oromucosal spray of nabiximols and intramuscular injection of botulinum toxin. The level of recommendation was weak for oral baclofen, tizanidine, gabapentin, benzodiazepines and transcranial magnetic stimulation. Conclusions: There is a clear need for new larger multicentre well‐designed clinical trials with a duration that allows the persistence of the effects and the long‐term safety of the interventions to be evaluated.